Massively-parallel Lagrangian particle code and applications - Yuan, Shaohua; Aguilar, Mario Zepeda; Naitlho, Nizar; Samulyak, Roman (Mechanics research communications, 2023)
Massively-parallel, distributed-memory algorithms for the Lagrangian particle hydrodynamic method (Samulyak et al., 2018) have been developed, verified, and implemented. The key component of parallel algorithms is a particle management module that includes a parallel construction of octree databases, dynamic adaptation and refinement of octrees, and particle migration between parallel subdomains. The particle management module is based on the p4est (parallel forest of k-trees) library. The massively-parallel Lagrangian particle code has been applied to a variety of fundamental science and applied problems. A summary of Lagrangian particle code applications to the injection of impurities into thermonuclear fusion devices and to the simulation of supersonic hydrogen jets in support of laser-plasma wakefield acceleration research has also been presented. •Massively-parallel, distributed-memory algorithms for Lagrangian particle method.•Particle manager based on parallel construction and dynamic adaptation of octrees.•Optimal load balance and good scalability on hundreds of cores.•Summary of applications to thermonuclear fusion and supersonic hydrogen jets.